Science exploration and instrumentation of the OKEANOS mission to a Jupiter Trojan asteroid using the solar power sail. (15th October 2018) - Okada, Tatsuaki; Kebukawa, Yoko; Aoki, Jun; Matsumoto, Jun; Yano, Hajime; Iwata, Takahiro; Mori, Osamu; Bibring, Jean-Pierre; Ulamec, Stephan; Jaumann, Ralf; ,
Abstract: An engineering mission OKEANOS to explore a Jupiter Trojan asteroid, using a Solar Power Sail is currently under study. After a decade-long cruise, it will rendezvous with the target asteroid, conduct global mapping of the asteroid from the spacecraft, and in situ measurements on the surface, using a lander. Science goals and enabling instruments of the mission are introduced, as the results of the joint study between the scientists and engineers from Japan and Europe. Highlights: OKEANOS is a mission to explore a Jupiter Trojan asteroid using a solar power sail. OKEANOS is a Jupiter Trojan rendezvous and landing mission, complementary to Lucy. Missing link to solar system formation and material evolution on a Jupiter Trojan. International instruments suitable for in-depth studies of a Jupiter Trojan.